Prevalence of micorganisms and antibiotics susptibility at burn unit of tertiary care hospital in southern Punjab - Alam, Iftikhar; Mujahid, Abdul Malik; Ghafoor, Hamad (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency of micro-organisms and their antibiotic susceptibility in acute burn wounds. Method: The retrospective, descriptive, cross-sectional study was conducted at the Department of Burn and Plastic Surgery, Allama Iqbal Teaching Hospital/Dera Ghazi Khan Medical College, Dera Ghazi Khan, Pakistan, and comprised data from January 2020 to December 2022 of patients of either gender aged 1-70 years with acute partial and full thickness burns. Those aged 1-14 years were designated as the paediatric group. Surface swab cultures were collected after 72 hours or upon signs of infection, and analysed using standard microbiological techniques. The prevalence of micro-organisms and antibiotic susceptibility was assessed using the disc diffusion method. Data was analysed using SPSS 22. Results: Of the 450 patients, 167(37.1%) were males and 179(39.8%) were females. The overall mean age was 23.95±11.83 years, and there were 104(23.1%) patients of paediatric age. Pseudomonas aeruginosa was the most common finding 157(34.9%), followed by klebsiella pneumonia 68(15%), methicillin-resistant staphylococcus aureus 68(15%), methicillin-sensitive staphylococcus aureus 45(10%), escherichia coli 23(5.1%), acinetobacter 13(2.9%) and proteus 5(1.1%). Among the pan-drug resistant strains, 67(14.9%) were pseudomonas and 22(4.9%) were klebsiella. Imipenem and linezolid were the most effective antibiotics overall. Conclusion: The most frequently isolated bacteria in burn wounds were pseudomonas aeruginosa, klebsiella pneumonia and staphylococcus aureus. Linezolid and imipenem were found to be the most effective against these isolates. Key Words: Burn wound infection, Antibiotic sensitivity, Culture sensitivity.